AKSI NYATA MUHAMMADIYAH DALAM SOLUSI PENDIDIKAN NASIONAL - ta tang (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
AbstractMuhammadiyah is an Islamic organization in Indonesia that contributes greatly in the field of education. The education sector is a Muhammadiyah charity that is rapidly developing. Exploration of philosophical concepts which is believed by Muhammadiyah is based on Islam, so as a logical consequence, Muhammadiyah tries and furthermore bases Muhammadiyah's educational philosophy on the philosophical principles that it believes in and adheres to. The philosophy of education manifests the foresight of the generation that will be raised. In this regard, the educational philosophy of Muhammadiyah cannot be separated from the philosophy of Islamic education, because what Muhammadiyah does is essentially Islamic principles which according to Muhammadiyah are the basis for the formation of Muslim human beings.